GIS to Support Cost-effective Decisions on Renewable Sources Applications for low temperature geothermal energy - Gemelli, Alberto; Mancini, Adriano; Diamantini, Claudia; Longhi, Sauro; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Through the results of a developed case study of information system for low temperature geothermal energy, GIS to Support Cost-effective Decisions on Renewable Sources addresses the issue of the use of Geographic Information Systems (GIS) in evaluating cost-effectiveness of renewable resource exploitation regional scale. Focusing on the design of a Decision Support System, a process is presented aimed to transform geographic data into knowledge useful for analysis and decision-making on the economic exploitation of geothermal energy. This detailed description includes a literature review and technical issues related to data collection, data mining, decision analysis for the informative system developed for the case study. A multi-disciplinary approach to GIS design is presented which is also an innovative example of fusion of georeferenced data acquired from multiple sources including remote sensing, networks of sensors and socio-economic censuses. GIS to Support Cost-effective Decisions on Renewable Sources is a pratical reference for engineers, managers and researchers involved in the design of GIS, decision support systems, investment planning/strategy in renewable energy and ICT innovation in this field.
PART I -- Preliminary Study -- 1.Decision environment of renewable energy: the case of geothermal energy -- 2.GIS supported decision making. -- PART II. Case Study -- 3.GIS supported decision making for low temperature geothermal energy in Central Italy -- 4.Data collection -- 5.Feature analysis: selecting decision criteria -- 6.Decision analysis: choosing the right plant -- 7.Regional atlas supporting the decision-making process -- 8.Conclusive remarks.
Keywords: Engineering; Hydraulic engineering; Renewable energy sources; Engineering; Geoengineering, Foundations, Hydraulics; Renewable and Green Energy; Energy Policy, Economics and Management; Energy Efficiency (incl. Buildings).